Novel paclitaxel-coated balloon angioplasty via single retrograde popliteal access for challenging superficial femoral artery and iliac artery lesions? - Cetin, Erdem; Unal, Celal Selcuk; Keskin, Aydın; Kartal, Hakan (Journal of Cardiology and Cardiovascular Medicine, 2019)
Objectives: We report our results regarding the use of BioPath™ paclitaxel-coated balloon catheters for superficial or distal external iliac artery revascularization via single retrograde popliteal access. Methods: We included 105 prospective consecutive patients. Single retrograde popliteal access was achieved under ultrasound guidance with the patients laid prone. An over-the-wire atherectomy system was used if risk of distal embolization was high due to plaque intensity of the target lesion. A 4 to 7 mm-diameter BioPath™ 035 balloon catheter was used for all lesions. Follow-up at 6th month included doppler ultrasound examination for patency. Results: Seventy-two patients (68.6%) had total SFA occlusion and 41 patients (39%) had concomitant external iliac artery involvement, out of whom 31 (29.5%) had total occlusion. Procedural success 90.5% for superficial femoral artery and 85.3% for external iliac artery. One-year patency rates in SFA and EIA were 84.8% and 80.4%, respectively Conclusion: Single retrograde popliteal access and drug-coated balloon angioplasty may offer a useful alternative to known modalities in treatment of challenging superficial femoral artery and concomitant iliac artery lesions.